Towards an ‘Interfaith Nationalism’? Christians and Their Relations to Muslims in the History Textbooks of the Syrian Arab Republic - Panos Kourgiotis (Religions, 2023)
This study examines how Christian–Muslim relations are presented in Syrian history textbooks and deployed by the embattled regime of Bashar al-Asad in its quest for legitimacy both at home and abroad since the eruption of the war that displaced half the country’s population. To that end, Critical Discourse Analysis is applied to selected texts from the school curricula stressing the harmonious coexistence between the country’s only two officially recognized faiths (Islam and Christianity), in addition to the Syrian Christians’ commitment to national unity from time immemorial, as nationalist discourses retrospectively assert. The historical narratives in question are juxtaposed with the ideological inconsistencies of the Arab nationalist Ba’th party that has ruled Syria since 1963 vis-à-vis religious sects and minorities, while being discussed against the backdrop of the recent geopolitical developments.